2006
DOI: 10.1097/01.wnr.0000234746.35195.b0
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide in cerebrospinal fluid and local inducible nitric oxide synthase after cauda equina compression in rats

Abstract: We investigated the time course of changes in nitric oxide metabolite (NO2- plus NO3-: NOx) levels in the cerebrospinal fluid and the expression of local inducible nitric oxide synthase following cauda equina compression in rats. Cerebrospinal fluid NOx levels were significantly increased from 12 h to 3 days after compression, and decreased thereafter. Histologically, inducible nitric oxide synthase immunoreactivity was observed in macrophages that infiltrated the dura mater on days 1 and 3 after compression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…These findings suggest that the [NOx] increases with chronic, but not subacute, spinal cord or cauda equina compression. In an animal experiment, we previously demonstrated that iNOS is expressed in macrophages and Schwann cells at the cauda equina compression site in rats [10]. Levy et al observed iNOS expression following chronic constriction injury to the sciatic nerve in rats [20].…”
Section: No Production Under Chronic Compression Of the Cauda Equina mentioning
confidence: 90%
See 1 more Smart Citation
“…These findings suggest that the [NOx] increases with chronic, but not subacute, spinal cord or cauda equina compression. In an animal experiment, we previously demonstrated that iNOS is expressed in macrophages and Schwann cells at the cauda equina compression site in rats [10]. Levy et al observed iNOS expression following chronic constriction injury to the sciatic nerve in rats [20].…”
Section: No Production Under Chronic Compression Of the Cauda Equina mentioning
confidence: 90%
“…Furthermore, the [NOx] in patients with SCI correlates with neurologic severity and recovery rate postoperatively, or with conservative treatment [9]. In animal models, inducible NO synthase (iNOS) is expressed in macrophages and Schwann cells at the cauda equina compression site [10] and in macrophages in the early stages after SCI [7]. Excessive NO production derived from iNOS has cytotoxic effects [11] and induces neuronal apoptosis secondary to neural degeneration and neurodysfunction [12].…”
Section: Introductionmentioning
confidence: 99%